Dampak Penggunaan Game Online Terhadap Interaksi Sosial (Studi Kasus Mahasiswa UAJY) - Pradipta, Aloysius Bagas; Ulfa, Marindah; Alexander, Leonardo; Sirait, Hema M; Danny, Alexander J (MEANS (Media Informasi Analisa dan Sistem), 2019)
Online games are entertainment media or playing media for children to adults. Online games have grown rapidly, especially in Indonesia. Online games are one of the most popular but have an impact on one's social interactions. The purpose of the research we conducted was to determine the effect of using online games on the FTI UAJY student social interactions and to find out the relationship between playing online games and the FTI UAJY student social interactions. The methodology we use is qualitative research, by taking samples from FTI UAJY students by distributing questionnaires and getting 239 active users of online game respondents. The results of the study know that online games influence student social interactions. Playing online games has a negative influence on the social interactions of FTI UAJY students. So that handling and control measures are needed. The handling and control measures are expected to emerge from the students themselves because only themselves can limit their activities such as playing online games with more positive activities.